Enhancing dermal and bone regeneration in calvarial defect surgery - Bruno Zanotti; Nicola Zingaretti; Daria Almesberger; Angela Verlicchi; Roberto Stefini; Mauro Ragonese; Gianni Franco Guarneri; Pier Camillo Parodi (Indian Journal of Plastic Surgery)
Introduction: To optimize the functional and esthetic result of cranioplasty, it is necessary to choose appropriate materials and take steps to preserve and support tissue vitality. As far as materials are concerned, custom-made porous hydroxyapatite implants are biomimetic, and therefore, provide good biological interaction and biointegration. However, before it is fully integrated, this material has relatively low mechanical resistance. Therefore, to reduce the risk of postoperative implant fracture, it would be desirable to accelerate regeneration of the tissues around and within the graft. Objectives: The objective was to determine whether integrating growth-factor-rich platelet gel or supportive dermal matrix into hydroxyapatite implant cranioplasty can accelerate bone remodeling and promote soft tissue regeneration, respectively. Materials and Methods: The investigation was performed on cranioplasty patients fitted with hydroxyapatite cranial implants between 2004 and 2010. In 7 patients, platelet gel was applied to the bone/prosthesis interface during surgery, and in a further 5 patients, characterized by thin, hypotrophic skin coverage of the cranial lacuna, a sheet of dermal matrix was applied between the prosthesis and the overlying soft tissue. In several of the former groups, platelet gel mixed with hydroxyapatite granules was used to fill small gaps between the skull and the implant. To confirm osteointegration, cranial computed tomography (CT) scans were taken at 3-6 month intervals for 1-year, and magnetic resonance imaging (MRI) was used to confirm dermal integrity. Results: Clinical examination performed a few weeks after surgery revealed good dermal regeneration, with thicker, healthier skin, apparently with a better blood supply, which was confirmed by MRI at 3-6 months. Furthermore, at 3-6 months, CT showed good biomimetism of the porous hydroxyapatite scaffold. Locations at which platelet gel and hydroxyapatite granules were used to fill gaps between the implant and skull appeared to show more rapid integration of the implant than untreated areas. Results were stable at 1-year and remain so to date in cases where follow-up is still ongoing. Conclusions: Bone remodeling time could be reduced by platelet gel application during cranioplasty with porous hydroxyapatite implants. Likewise, layering dermal matrix over such implants appears to promote dermal tissue regeneration and the oshtemo mimetic process. Both of these strategies may, therefore, reduce the likelihood of postsurgical fracture by promoting mechanical resistance.